Lebesgue Integral Inequalities of Jensen Type for Î»-Convex Functions - Dragomir, Silvestru Sever (Armenian Journal of Mathematics, 2018)
Some Lebesgue integral inequalities of Jensen type for Î»-convex functions defined on real intervals are given.
Keywords: Convex functions, Discrete inequalities, Î»-Convex functions, Jensen's type inequalities